The pandemic’s cruel aftermath: progressive decline in spay/neuter capacity - Guerios, Simone D.; Clemmer, Gina; Levy, Julie K. (Frontiers in Veterinary Science, 2025)
The COVID-19 pandemic lockdown in early 2020 resulted in a temporary suspension of elective spay and neuter procedures in many low-cost spay/neuter clinics. In our previous study, we projected a deficit of 2.7 million surgeries performed in high-quality high-volume spay-neuter (HQHVSN) clinics as a result of the shutdown and subsequent inability to recover to pre-pandemic productivity by the end of 2021. The purpose of this follow-up study was to determine whether the clinics subsequently recovered and caught up with the previously delayed procedures. Spay-neuter data were collected from 212 HQHVSN clinics from January 2019 through June 2023. The clinics collectively performed 1,217,240 spay/neuter surgeries in the pre-COVID baseline year of 2019. The pandemic triggered a reduction of 13% in 2020, 3% in 2021, 6% in 2022, and 1% in the first half of 2023. Analysis of patient data from the same clinics in our previous report revealed that instead of rebounding to pre-pandemic surgery capacity, they performed even fewer surgeries per quarter in the 18-month follow-up period than they did in 2021. If similar trends occurred in the estimated 3,000 spay-neuter clinics across the United States, the deficit in spay-neuter surgeries is estimated to have risen to 3.7 million surgeries, not including the compounding effect of those intact animals producing litters of their own. The continued decline in low-cost spay-neuter year over year impedes access to basic preventive pet healthcare and threatens to undermine decades of progress in controlling pet overpopulation.